1999
DOI: 10.1097/00000539-199910000-00025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous or Subarachnoid Lidocaine on Glutamate Accumulation During Transient Forebrain Ischemia in Rats

Abstract: IV or subarachnoid lidocaine was demonstrated to suppress glutamate accumulation in the hippocampus and the cortex during transient forebrain ischemia in rats by using the dialysis electrode method. Lidocaine can have a neuroprotective effect through the suppression of the increase in extracellular glutamate concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…These reported ionic and membrane events could be the explanation to the strong increase in the time constant for voltage decay induced by lidocaine. The fact that lidocaine did not change brain impedance under normal normoxic conditions but did so during ischemia reducing the progression of edema, detected by its most important sign, change in tissue impedance [18][19][20][21] , strongly supports the notion of the neuroprotective effect of lidocaine, which agrees with other reported brain-protective actions of lidocaine in experimental [28][29][30] , neuropathological [26,31] and clinical studies [32,33] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These reported ionic and membrane events could be the explanation to the strong increase in the time constant for voltage decay induced by lidocaine. The fact that lidocaine did not change brain impedance under normal normoxic conditions but did so during ischemia reducing the progression of edema, detected by its most important sign, change in tissue impedance [18][19][20][21] , strongly supports the notion of the neuroprotective effect of lidocaine, which agrees with other reported brain-protective actions of lidocaine in experimental [28][29][30] , neuropathological [26,31] and clinical studies [32,33] .…”
Section: Discussionsupporting
confidence: 81%
“…This mechanism may in turn activate intracellular signaling cascades that lead to altered expression of protective genes [34] . Activation of NMDA channels, mitochondrial Na + /Ca 2+ cotransporters and synaptic glutamate liberation [4,28,29,31] are processes strongly associated with the early formation of cytotoxic edema [17,20] and when blocked or reduced by lidocaine could explain results reported in the present report.…”
Section: Discussionsupporting
confidence: 52%
“…Mechanisms of action of intravenous (IV) lidocaine include the suppression of autonomic reflexes, a neuronal membrane stabilizing effect and inhibition of the release of excitatory neuroamines, particularly glutamate (Terada et al. ). In humans, IV lidocaine administration prior to intubation has been shown to reduce the pressor response (Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the penumbra, PIDs are thought to be generated by glutamate and potassium released from the ischemic core (Mies et al, 1994;Dirnagl et al, 1999). Previous studies have reported that administration of lidocaine did not suppress glutamate release at doses < 5 mg/kg (Terada et al, 1999). Since the lidocaine was infused at the rate of 2 mg/kg/h (total dose: 5 mg/kg in 150 min) in this study, glutamate release was not likely to be suppressed.…”
Section: Discussionmentioning
confidence: 63%